Factors affecting the intention to purchase halal cosmetics on Instagram: E-WOM and brand image - Muhammad Farid Wajdi; Hendy Mustiko Aji; Suwarsono Muhammad (Faculty of Business & Economics, Universitas Islam Indonesia, 2020)
Purpose: This research is conducted to understand the effect of E-WOM and brand image on purchase intention of halal cosmetics which are sold online through Instagram.Methodology: This research is quantitative research. The data used in this research is primary data which is collected using a questionnaire. The sampling technique is purposive sampling with 93 research samples.Findings: This research shows that the purchase intention of halal cosmetics through Instagram is simultaneously influenced by E-WOM and brand image. This finding support previous researches related to the effect of E-WOM and brand image on purchase intention.Originality/Value: This research is a replication-based model and is adapted from published research. The originality in this research is in the context of object and location. Various halal cosmetics that are being sold online through Instagram are the main focus to be researched on. This main focus has not been being researched beforehand.